Gas Barrier Coating
A polyvinyl alcohol and polyacrylic acid barrier coating addresses the need for metallization-free gas barrier performance in food packaging by maintaining low oxygen transmission rates and enhancing recyclability.
Patent Information
- Application Number
- JP2024531614
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-07
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-26
AI Technical Summary
Existing food packaging solutions rely on metallization for gas barrier performance, which increases energy consumption and negatively impacts recyclability, necessitating a metallization-free solution that maintains or improves gas barrier performance while enhancing recyclability.
A barrier coating comprising polyvinyl alcohol and polyacrylic acid, formed at temperatures below 100°C, which can be applied to various substrates including polyethylene, polypropylene, and polyethylene terephthalate, providing effective gas barrier performance without metallization.
The coating achieves low oxygen transmission rates (OTR) of less than 1 cc/m²/day at relative humidity above 50%, improving recyclability and reducing energy consumption.
Smart Images

Figure 2024546616000001 
Figure 2024546616000002 
Figure 2024546616000003
Abstract
Description
[Technical field]
[0001] Priority This application claims the benefit of International Application No. PCT / CN2021 / 136058, filed December 7, 2021.
[0002] The present disclosure relates to barrier field coatings. More specifically, the present disclosure relates to barrier field coatings that include PVOH.
[0003] Introduction The standard approach in food packaging applications to achieve the required gas barrier performance is the use of metallized films. Most of the energy used in the manufacturing and packaging process is used in the metallization. If metallization is used, which adds a processing step, the application of a primer is necessary. The amount of these added materials also negatively impacts recyclability. Thus, there is an urgent need for a scalable solution that provides good OTR performance but does not rely on metallization, and therefore improves recyclability without sacrificing OTR performance. Summary of the Invention
[0004] Disclosed herein is a barrier coating comprising polyvinyl alcohol and polyacrylic acid, the barrier film being formed at or below 100° C. Also disclosed is a laminate comprising a barrier coating comprising polyvinyl alcohol and polyacrylic acid, the barrier film being formed at or below 100° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0005] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed.
[0006] Numerical ranges disclosed herein include all values between the lower limit and the upper limit (inclusive). In the case of ranges containing explicit values (e.g., ranges 1, or 2, or 3-5, or 6, or 7), any subranges between any two explicit values are included (e.g., the range 1-7 above includes the subranges 1-2, 2-6, 5-7, 3-7, 5-6, etc.).
[0007] The term "composition" refers to a mixture of materials that make up the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0008] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer encompasses the term homopolymer (used to refer to a polymer prepared from only one type of monomer), and the terms copolymer or interpolymer. Trace amounts of impurities (e.g., catalyst residues) may be incorporated in and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.
[0009] As used herein, the term "polyolefin" means a polymer that contains, in polymerized form, a majority of olefin monomers, such as ethylene or propylene (based on the weight of the polymer), and may optionally contain one or more comonomers.
[0010] "Polyethylene polymer", "polyethylene-based polymer", "PE-based polymer", "polyethylene", or "ethylene-based polymer" is intended to mean a polymer that contains a majority of units derived from ethylene monomer (>50 mol%, or >60 mol%, or >70 mol%, or >80 mol%, or >90 mol%, or >95 mol%, or >97 mol%). This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), which includes both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE). These polyethylene materials are generally well known in the art. However, the following description may be helpful in understanding the differences between some of these different polyethylene resins.
[0011] The term "LDPE", which may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene", is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) using a free radical initiator, such as a peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated herein by reference). LDPE resins typically have a density in the range of 0.916 to 0.935 g / cm3.
[0012] The term "LLDPE" includes both resins made using traditional Ziegler-Natta and chromium-based catalysts, as well as single-site catalysts, including, but not limited to, bis-metallocene catalysts (sometimes referred to as "m-LLDPE") and constrained geometry catalysts, and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers, as further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent 4,076,698, and / or blends thereof (such as those disclosed in U.S. Patents 3,914,342 or 5,854,045). LLDPE can be made via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0013] The term "MDPE" refers to polyethylene having a density of 0.926 to 0.935 g / cm3. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to bis-metallocene and constrained geometry catalysts, and typically has a molecular weight distribution ("MWD") greater than 2.5.
[0014] The term "HDPE" refers to polyethylene having a density greater than about 0.935 g / cm3 to about 0.970 g / cm3 that is generally prepared using a single-site catalyst, including, but not limited to, Ziegler-Natta, chromium, or bis-metallocene and constrained geometry catalysts.
[0015] The term "ULDPE" generally refers to polyethylene having a density between 0.880 and 0.912 g / cm3 that is prepared with a single-site catalyst, including but not limited to Ziegler-Natta, chromium, or bis-metallocene and constrained geometry catalysts.
[0016] "Polypropylene-based polymer", "PP-based polymer", or "polypyrene-based polymer" is intended to mean a polymer that contains a majority (>50 mol%, or >60 mol%, or >70 mol%, or >80 mol%, or >90 mol%, or >95 mol%) of units derived from polypyrene monomers.
[0017] "Polyethylene terephthalate-based polymer" or "PET-based polymer" is intended to mean a polymer that contains a majority amount (>50% by weight, or >60% by weight, or >70% by weight, or >80% by weight, or >90% by weight, or >95% by weight) of ethylene terephthalate.
[0018] A "polyolefin plastomer" can be a polyethylene plastomer or a polypropylene plastomer. Polyolefin plastomers include, for example, polymers made using single-site catalysts, such as metallocene and constrained geometry catalysts. Polyolefin plastomers have a viscosity of 0.885 to 0.915 g / cm 3 It has a density of 0.885g / cm 3 ~0.915g / cm 3 All individual values and subranges are included herein and disclosed herein. For example, the density of the plastomer may be 0.895, 0.900, or 0.905 g / cm 3 from the lower limit of 0.905, 0.910, or 0.915 g / cm 3 In some embodiments, the polyolefin elastomer has a viscosity of 0.890 to 0.910 g / cm 3 has a density of
[0019] The "polyolefin elastomer" may be a polyethylene elastomer or a polypropylene elastomer. The polyolefin elastomer has a modulus of 0.857 to 0.885 g / cm 3 It has a density of 0.857g / cm 3 ~0.885g / cm 3 All individual values and subranges are included herein and disclosed herein. For example, low density polyethylene has a density of 0.857, 0.860, 0.865, 0.870, or 0.875 g / cm 3 From the lower limit of 0.870, 0.875, 0.880, or 0.885 g / cm 3 In some embodiments, the polyolefin elastomer has a viscosity of 0.860 to 0.880 g / cm 3 has a density of
[0020] "Polyethylene-based film" or "PE-based film" refers to a film that contains at least 90 weight percent polyethylene, at least 95 weight percent polyethylene, or at least 97 weight percent polyethylene, based on the total weight of the film.
[0021] "Polypropylene-based film" or "PP-based film" refers to a film that contains at least 90 weight percent polypropylene, at least 95 weight percent polypropylene, or at least 97 weight percent polypropylene, based on the total weight of the film.
[0022] "Polyethylene terephthalate-based film" or "PET-based film" refers to a film that contains at least 90 weight percent polyethylene terephthalate, at least 95 weight percent polyethylene terephthalate, or at least 97 weight percent polyethylene terephthalate, based on the total weight of the film.
[0023] As used herein, an antioxidant is a compound that is included in a polymer film to stabilize the polymer(s) or prevent oxidative degradation of the polymer(s). Antioxidants are well known to those skilled in the art.
[0024] As used herein, an anti-blocking agent is a compound that minimizes or prevents sticking (i.e., adhesion) between two adjacent layers of a film. Sticking can cause problems, for example, during unwinding of a film roll. The use of anti-blocking agents is well known to those skilled in the art. Examples of common anti-blocking agents include, but are not limited to, silica, talc, calcium carbonate, and combinations thereof.
[0025] As used herein, slip agents are compounds added to films to reduce friction between films and / or between the film and equipment. Typical slip agents include migratory and non-migratory slip agents and are well known to those skilled in the art.
[0026] As used herein, the term "copolymer" means any polymer having two or more types of monomers.
[0027] As used herein, the term "polyvinyl alcohol" means a polymer of vinyl alcohol. Modified polyvinyl alcohols, such as ethylene modified polyvinyl alcohol, are specifically included in this definition.
[0028] Barrier Coating Disclosed herein is a barrier coating in which a barrier film is formed at or below 100°C. The barrier coating can include polyvinyl alcohol and polyacrylic acid. The barrier coating can include a ratio of polyvinyl alcohol to polyacrylic acid of 95:5 to 5:95. The barrier coating can include a ratio of polyvinyl alcohol to polyacrylic acid of 30:70 to 70:30. The barrier coating can include aqueous coating additives such as, but not limited to, antiblocking agents, defoamers, thickeners, and wetting agents.
[0029] The barrier coating provides a thermal conductivity of 0.60 cc / m at 50% or greater relative humidity. 2 The coated substrate can have an OTR of 0.60 to 0.02 cc / m at 50% or greater relative humidity. 2 The barrier coating may have an OTR of 0.02-0.1 or 0.02-0.03 cc / m. All internal values and subranges are disclosed. For example, the substrate coated with the barrier coating may have an OTR of 0.02-0.1 or 0.02-0.03 cc / m. 2 The barrier coating can be applied to a variety of substrates, including but not limited to polyethylene, polypropylene, and polyethylene terephthalate.
[0030] Polyacrylic acid The polyacrylic acid may comprise at least one poly(meth)acrylic acid. The polyacrylic acid may comprise a copolymer of at least two polymers. The polyacrylic acid may comprise a copolymer of at least two monomers. The polyacrylic acid may comprise a mixture of at least two polymers.
[0031] Polyacrylic acid has a number average molecular weight (M n ) all internal values and subranges are included. For example, polyacrylic acid may have a number average molecular weight (M) of 20,000 to 300,000 or 40,000 to 200,000 g / mol. n).
[0032] The polyacrylic acid can be partially neutralized. The polyacrylic acid can have a degree of neutralization of 2-50%. All internal values and subranges are included. For example, the polyacrylic acid can have a degree of neutralization of 5-20%. The polyacrylic acid can be partially neutralized using bases including, but not limited to, NaOH, KOH, NH3·H2O, ZnO, and CaO.
[0033] Polyvinyl alcohol The polyvinyl alcohol may be ethylene modified. The polyvinyl alcohol may contain less than 5% ethylene. The polyvinyl alcohol may have a degree of saponification of at least 80%. The polyvinyl alcohol may have a degree of saponification of at least 95%. The polyvinyl alcohol may have a degree of saponification of 80-100%. All internal values and subranges are included. For example, the polyvinyl alcohol may have a degree of saponification of 95-100%.
[0034] The polyvinyl alcohol can have a molecular weight of 10,000 to 300,000 g / mol. All internal values and subranges are disclosed. For example, the polyvinyl alcohol can have a molecular weight of 10,000 to 100,000 g / mol.
[0035] The polyvinyl alcohol resin has a degree of saponification of at least 80% and a molecular weight (M) of 10,000 to 300,000 g / mol. w The polyvinyl alcohol may have a degree of saponification of at least 95% and a molecular weight (M) of 10,000 to 100,000 g / mol. w ).
[0036] Base material The substrate may include a film. The film may have at least one layer that includes polyethylene. The other layer may be PP, nylon, or other plastics known to those skilled in the art. There may be one layer. Alternatively, there may be two or more layers. These two or more layers may be extruded together to form a film. There may be three (or more) layers. When there are three (or more) layers, the outer layer is called the sealant layer, the layer opposite the sealant layer is called the skin layer, and the layer or layers between the skin layer and the sealant layer are the core layer or layers. When there is only one layer that includes, any of the compositions described herein as skin layer, core layer, or sealant layer can be used. When there are only two layers, any combination of skin layer and core layer, skin layer and sealant layer, or core layer and sealant layer can be used. When there are two or more layers, each layer can be directly adjacent to at least one other layer or adhesive layer. The film can include a sealant layer. The film may include a skin layer, a core layer and a sealant layer.
[0037] The film can include linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), as well as combinations of two or more of the foregoing.The film can include Ziegler-Natta catalyzed, single-site catalyzed (including but not limited to metallocene), or chromium catalyzed linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), autoclave produced or tubular produced low density polyethylene (LDPE), as well as combinations of two or more of the foregoing.
[0038] The film may further comprise at least one of very low density polyethylene, polyolefin plastomer, polyolefin elastomer, ethylene vinyl acetate copolymer, ethylene ethyl acrylate copolymer, ethylene vinyl alcohol, and any polymer comprising at least 50% ethylene monomer, and combinations thereof.
[0039] The skin layer can include polypropylene, nylon, linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), and combinations of two or more of the foregoing. The LLDPE can be single-site catalyzed polyethylene (such as, but not limited to, m-LLDPE). The skin layer can further include additives such as, for example, antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and blowing agents.
[0040] The core layer can include linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), as well as combinations of two or more of the foregoing.
[0041] The sealant layer may comprise linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), low density polyethylene (LDPE), polyolefin elastomers or plastomers, as well as combinations of two or more of the foregoing. The sealant layer may comprise Ziegler-Natta catalyzed, single-site catalyzed (including metallocene), or chromium catalyzed linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), autoclave-produced or tubular-produced low density polyethylene (LDPE), as well as combinations of two or more of the foregoing. The LLDPE may be a single-site catalyzed polyethylene (such as mLLDPE). This may be an outer layer of the film. The sealant layer may advantageously comprise an antiblocking agent. For example, the antiblocking agent may be present in the sealant layer in an amount of at least about 200 ppm, at least about 1000 ppm, or at least about 1500 ppm. Additionally, slip agents (e.g., erucamide) may be beneficial. For example, the slip agent may be present in the sealant layer in an amount less than 500 ppm, or less than 300 ppm, or less than 200 ppm, less than 100 ppm, or equal to 0 ppm, based on the total weight of the sealant layer.
[0042] The film may be a blown film, a cast film, a machine direction stretched film, or a biaxially stretched film. The film may be made by blown, cast, water quenched, double bubble, or other techniques known to those skilled in the art, such as those described in Film Processing Advances, Toshitaka Kanai and Gregory A. Campbell (editors), Chapter 7 (Biaxial Oriented Film Technology), pp. 194-229. After making, the film may be subjected to a machine direction orientation (MDO) or biaxial stretching process to provide a machine direction stretched film or a biaxially stretched film, respectively.
[0043] The total thickness of the film can be at least 10 micrometers, at least 20 micrometers, or at least 30 micrometers. The total thickness of the film can be no more than 200 micrometers, no more than 150 micrometers, no more than 120 micrometers, no more than 100 micrometers, no more than 80 micrometers, no more than 70 micrometers, or no more than 60 micrometers.
[0044] The concentration of the antioxidant in the film layer is less than 3000 ppm, or less than 2000 ppm, or less than 1500 ppm, or less than 1300 ppm, based on the total weight of the film.
[0045] Creation and Use Solutions of PVOH and various bases can be obtained as understood in the art. Partially neutralized PAA can be prepared by adding a calculated amount of base solution to the PAA solution. The amount of base added depends on the desired degree of neutralization and the moles of PAA carboxyl groups present in the sample to be neutralized. The partially neutralized PAANa can then be mixed with PVOH using methods understood in the art to obtain a barrier coating.
[0046] The solutions thus produced can be coated onto a variety of substrates, such as polyethylene, polypropylene, or polyethylene terephthalate, at various film thicknesses depending on the application, using a variety of means known in the art, such as roll coating, gravure coating, flexo coating, and bar coating. The resulting coated substrates are useful in food packaging and any other application where an oxygen impermeable barrier is required.
[0047] Test Method Vapor sorption The thin film samples are dried at 60°C for 24 hours. Each sample is then peeled from the substrate and weighed before testing. The test is performed at room temperature with the relative humidity increasing from 0% to 80% in 10% intervals. The equilibrium weight at each relative humidity is then recorded and the vapor sorption rate can be calculated.
[0048] Oxygen permeability The oxygen transmission rate of the blend films was measured at 23° C. and 50% relative humidity according to ASTM D3985-05 using a MOCON Ox-Tran Model 2 / 21.
[0049] Molecular weight measurement Prepare the polymer solution at a concentration of approximately 1-2 mg / mL in 20 mM NaH2PO4 / Na2HPO4 at pH 7. Allow the sample to dissolve on a mechanical shaker for approximately 2 h at ambient temperature. Filter the polymer solution into an autosampler vial using a 0.2 mm PVDF filter. The sample should appear soluble and no resistance should be observed during filtration.
[0050] Size exclusion chromatography (SEC) separation is performed on a Waters APC system consisting of an isocratic pump-degasser, autosampler, and RI detector operated at 40°C. Sec separation is performed on two TSKgel columns with GMPWXL and G2500PWXL pore sizes and 13 μm and 7 μm particle sizes in Na2HPO4 at pH 7. The SEC system / column set is calibrated with narrow poly(acrylic standards) (PAA). 20 mL of sample solution is injected into the column set for SEC separation. System control, data acquisition, and data processing are performed using Empower® software version 3.0. EXAMPLES
[0051] The materials used in the inventive examples and comparative samples are shown below in Table 1. All DOW™ commercial samples are available from DOW™ Chemical.
[0052] [Table 1]
[0053] Preparation of PVOH 10 parts of RS2117 are dissolved in 90 parts of deionized water by stirring at 90° C. for 3 hours. The clear PVOH solution thus obtained with a solid content of 10% is then cooled to room temperature.
[0054] Preparation of NaOH solution A clear NaOH solution with 10% solids is obtained by stirring 10 parts NaOH in 90 parts deionized water for 15 minutes.
[0055] Neutralized PAA solution The neutralized PPA solutions shown in Table 2 are prepared by adding a calculated amount of sodium hydroxide solution to a 25 wt% solution of polyacrylic acid having a number average molecular weight of 20,000 and Mw of about 67,000. A calculated amount of sodium hydroxide solution is added separately to portions of the aqueous solution of PAA in terms of moles of PAA carboxyl groups to obtain partially neutralized products (PAANa) with degrees of neutralization (DN) of 5%, 10%, 20%, 25% and 50%, respectively.
[0056] [Table 2]
[0057] The neutralized polyacrylic acid solution is bar coated onto 50 μm thick PET using a Meyer bar automatic film coating device that precisely controls the film thickness. The coated film is dried at 100 °C for 2 min. The dried film thickness was controlled to 10 ± 2 μm.
[0058] Table 3 shows the oxygen barrier performance of two different types of PAA with various molecular weights and different degrees of neutralization. The lowest OTR for PET substrate is 0.07 cc / m at 10 μm thickness. 2 It is evaluated in days.
[0059] [Table 3]
[0060] Various weight ratios shown in Table 4 are prepared by mixing 10% neutralized PAANa with PVOH, all with a final solids content of 10%. The mixed solutions, all with a final solids content of 10%, are bar coated onto a 50 μm thick PET substrate using a Meyer bar automated film coating device that precisely controls the film thickness to 10±2 μm. The coated film is dried at 100° C. for 2 minutes.
[0061] [Table 4]
[0062] PVOH and 10% neutralized PAANa are mixed in a weight ratio of 7:3 to obtain an aqueous mixed solution with a final solid content of 10%. These solutions are then bar coated onto 25 μm HDPE using a Meyer bar automatic film coating device that precisely controls the film thickness to 5±2 μm. The coated film is then dried at 40° C. for 5 minutes. The results are shown in Table 5.
[0063] [Table 5]
[0064] The results shown in Tables 2 to 5 are summarized in Table 6 below.
[0065] [Table 6]
Claims
1. 1. A barrier coating comprising polyvinyl alcohol and polyacrylic acid, wherein the barrier film is formed at or below 100°C.
2. 10. The barrier coating of claim 1, wherein the polyacrylic acid comprises at least one poly(meth)acrylic acid.
3. The polyacrylic acid has a number average molecular weight (M n 3. The barrier coating of claim 1 or 2, having a
4. The polyacrylic acid has a number average molecular weight (M n 4. The barrier coating of claim 1, wherein the barrier coating comprises a
5. The polyacrylic acid has a number average molecular weight (M n 5. The barrier coating of claim 1, wherein the barrier coating comprises a
6. 6. The barrier coating of claim 1, wherein the polyacrylic acid is partially neutralized.
7. 7. A barrier coating according to any one of claims 1 to 6, wherein the polyacrylic acid has a degree of neutralization of 2 to 50%.
8. 8. A barrier coating according to any one of claims 1 to 7, wherein the polyvinyl alcohol has a degree of saponification of at least 80%.
9. 9. A barrier coating according to any one of claims 1 to 8, wherein the polyvinyl alcohol has a degree of saponification of at least 95%.
10. The polyvinyl alcohol has a molecular weight (M w 10. The barrier coating of claim 1, having a molecular weight of 1.5 or more.
11. The polyvinyl alcohol has a molecular weight (M w 11. The barrier coating of claim 1, having a molecular weight of 1.0 or more.
12. 12. The barrier coating of any one of claims 1 to 11 comprising a ratio of polyvinyl alcohol to polyacrylic acid of from 95:5 to 5:
95.
13. 13. The barrier coating of any one of claims 1 to 12 comprising a ratio of polyvinyl alcohol to polyacrylic acid of from 30:70 to 70:
30.
14. 14. The barrier coating of any of claims 1 to 13, wherein the polyvinyl alcohol comprises ethylene modified polyvinyl alcohol.
15. A substrate comprising the barrier coating of claim 1.
Citation Information
Patent Citations
Gas barrier film and its production
JP1995102083A
Gas barrier laminate and its manufacturing method
JP2005144761A
Gas barrier laminated film
JP2007083409A
Gas barrier laminated film
JP2007090874A
Gas barrier laminated film, gas barrier multi-layer film, and method for manufacturing them
JP2007313758A
